Exposure of children to metals via tap water ingestion at home: Contamination and exposure data from a nationwide survey in France. (September 2016) - Le Bot, Barbara; Lucas, Jean-Paul; Lacroix, Françoise; Glorennec, Philippe
Abstract: 29 inorganic compounds (Al, As, B, Ba, Be, Bi, Ca, Cd, Ce, Co, Cr, Cu, Fe, Gd, K, Mg, Mn, Mo, Na, Nd, Ni, Pb, Sb, Se, Sr, Tl, U, V and Zn) were measured in the tap water of 484 representative homes of children aged 6 months to 6 years in metropolitan France in 2008–2009. Parents were asked whether their children consumed tap water. Sampling design and sampling weights were taken into account to estimate element concentrations in tap water supplied to the 3, 581, 991 homes of 4, 923, 058 children aged 6 months to 6 years. Median and 95th percentiles of concentrations in tap water were in μg/L: Al: < 10, 48.3, As: 0.2, 2.1; B: < 100, 100; Ba: 30.7, 149.4; Ca: 85, 000, 121, 700; Cd: < 0.5, < 0.5; Ce: < 0.5, < 0.5; Co: < 0.5, 0.8; Cr: < 5, < 5; Cu: 70, 720; K: 2210, 6740; Fe: < 20, 46; Mn: < 5, < 5; Mo: < 0.5, 1.5; Na: 14, 500, 66, 800; Ni: < 2, 10.2; Mg: 6500, 21, 200; Pb: < 1, 5.4; Sb: < 0.5, < 0.5; Se: < 1, 6.7; Sr: 256.9, 1004; Tl: < 0.5, < 0.5; U: < 0.5, 2.4; V: < 1, 1; Zn: 53, 208. Of the 2, 977, 123 young children drinking tap water in France, some were drinking water having concentrations above the 2011 World Health Organization drinking-water quality guidelines: respectively 498 (CI 95%: 0–1484) over 700 μg/L of Ba; 121, 581 (CI 95%: 7091–236, 070) over 50 mg/L of Na; 2044 (CI 95%: 0–6132) over 70 μg/L of Ni, and 78, 466 (17, 171–139, 761) over 10 μg/L of Pb. Since it is representative, this tap water contamination data can be used for integrated exposure assessment, in conjunction with diet and environmental (dust and soil) exposure data. Highlights: First representative estimates of 29 inorganic elements in tap water of homes with young children in France Most children drank tap water meeting regulatory requirements Pb in tap water has decreased but remains of concern